NARRATING LOCAL WISDOM AND ETHNIC IDENTITY THROUGH DIGITAL FOLKLORE IN TIMUN MAS AND THE LITTLE RED RIDING HOOD - Nur Asiyah; Hidayatul Nurjanah; Elga Lauris Zabrina; Fuad Muhammad Zein (2025)
Digital storytelling continues to shape how cultures are preserved and shared, making examining folklore in both its traditional and digital forms essential to sustain ethnic identity, local wisdom, and cultural literacy. This study explores how local wisdom and ethnic identity are narrated through digital folklore in the Indonesian story of Timun Mas and the Western tale of The Little Red Riding Hood. Utilizing Jan Harold Brunvand's folklore theory and ethnic literature as theoretical frameworks, the research employs a descriptive qualitative method with an American Studies approach. The primary data consists of words, phrases, and sentences from these two folkloric children's stories. The analysis reveals that Timun Mas embodies spiritual resilience, ancestral wisdom, and a harmonious relationship with nature, highlighting key aspects of Indonesian local wisdom. Meanwhile, The Little Red Riding Hood emphasizes awareness, self-restraint, and personal responsibility in confronting danger, reflecting values prominent in Western cultural contexts. These findings confirm that both stories serve as cultural tools to convey and reinforce ethnic identity through their narratives, characters, and cultural symbols. Digital transformation makes cultural values more accessible and relevant to today’s generation. The interaction between tradition and digitalization plays a key role in preserving cultural heritage in the modern era. The findings suggest that digital folklore can strengthen cultural literacy and ethnic identity. Future research is encouraged to explore transmediality and comparative literature to better understand how local and global values are negotiated through evolving narrative forms.